Gammeltestamentlige læsninger og kirkeår i Danmark på reformationstiden - Villadsen, Holger (Kirkehistoriske Samlinger, 2010)
Summary Readings from the Old Testament and the Liturgical Year in the Danish Reformation This article analyses four documents from Denmark before and after the Reformation in 1536 with special focus on patterns in the use of readings from the Old Testament in the Eucharist and their connexion with changes in the Liturgical Year. Missale Lundense (1514) is used as a representative of the Danish liturgical tradition before the Reformation. It is considered as a relevant source since it was intended for use in the Danish archdiocese just before the Reformation, and it is a practical choice since it in 1946 was printed in facsimile (Missale Lundense av år 1514, Malmø 1946). A list is given of the first reading (or readings) in the first part of the Liturgical Year, proprium de tempore, with exclusion of the gospel. There are in this part of the missal 203 days with 248 readings (lectio), and of these are 103 from the Old Testament and 145 from the New Testament (the gospels excluded). It is demonstrated that readings from the Old Testament not are used on Sundays (with one exception), but only on weekdays, mostly in Lent and on Ember days. The normal structure is two readings: lectio and gospel. The lectio can be taken from the New or the Old Testament. There are days with three or more readings, but no clear examples of the supposed original lectionary structure with three readings: Old Testament, epistle and gospel. The second document is a book in three parts with sermons of Hans Tausen (1494-1561), one of the leading Danish reformers. The book, Postillen, contains not only sermons but also the liturgical readings for the Mass in Danish translation, and this translation of the readings was probably in common liturgical use in the first years after the reformation. The book was printed in 1539, but was probably written in 1536 or earlier. A list of the Liturgical Year and the epistles shows that the Liturgical Year is much reduced in comparison with the former tradition in the missals and mostly consists of the Sundays with an epistle from the New Testament. The readings are mostly identical with the readings in Missale Lundense, but since most of the weekdays with readings from the Old Testament are left out, the number of readings from the Old Testament is much reduced. Only seven are found, five from the old tradition and two new. On the preserved days, where a reading from the Old Testament was found in Missale Lundense, the same reading is mostly found on the same day in Postillen. The third document is the official Danish Church Order after the Reformation, Kirkeordinansen (preliminary Latin version 1537, final Danish version 1539). Here is found decisions concerning the Liturgical Year, which determined the liturgical days for the next centuries in Denmark. Besides the Sundays there was Mass on Christmas, Easter, Pentecost, New Year, Epiphany, Purification of Mary, Annunciation, Ascension Day, Visitation of Mary, John the Baptist, Michael and All Saints’ Day. The Liturgical Year in Kirkeordinansen corresponds closely to that in Postillen by Hans Tausen. The Church Order has in general no rules concerning the readings, but refer to the usual readings. The indirect consequence of the reduction of the Liturgical Year combined with the usual readings was, that readings from the Old Testament almost disappeared, but there is not in Kirkeordinansen traces of an intention to eliminate readings from the Old Testament. On the contrary: on the day of the Visitation of Mary a new reading from the Old Testament (Is. 11.1-10) is chosen in stead of the old one (Cant. 2.8-14). The final document is the new standard liturgical book in the Danish Reformation edited by Peder Palladius (1503-1560), who was bishop of Sealand from 1537. In 1556 he edited a book, which contained all the liturgical texts necessary for services in the church, including readings for all days in the Liturgical Year. The readings were taken from the new Danish Bible translation (1550). The traditional Danish name for the book is Alterbog, which means a book to be used at the altar in the Church. In practise it replaced the old missals, and the Alterbog established a new standard, which has been followed in the Danish Church since. The Liturgical Year in Palladius’ Alterbog 1556 follows Kirkeordinansen from 1537/1539 (and Hans Tausen’s Postille from 1539). There are only minor additions. A list of the days in the Liturgical Year and the first readings shows minor differences compared with Missale Lundense and Hans Tausen’s Postille, but mostly the readings are the same. The number of days with readings from the Old Testament is low, only five days: Epiphany (Is. 60.1-6), Purification of Mary (Mal. 3.1-4), Annunciation (Is. 7.10-15), John the Baptist (Is. 49,1-6) and Visitation of Mary (Is. 11,1-10). The first four are (mostly) the same as in Missale Lundense 1514. Compared with Postillen by Hans Tausen two readings from the Old Testament are replaced by readings from the New Testament on the last Sundays of the Liturgical Year. In the Alterbog by Peder Palladius only readings from the New Testament are used on Sundays. The conclusion of the analysis of the use of readings from the Old Testament in the Danish Reformation is, that a pattern for the use of readings from the Old Testament can be found in the old tradition represented by Missale Lundense 1514: they are not used on Sundays, but only on weekdays, mostly in Lent and on Ember days. The Danish Reformation followed the pattern from the older tradition and did mostly not choose new readings, but preserved the old. When the Liturgical Year in the Reformation was reduced, mostly to Sundays, the result of the old pattern was, that readings from the Old Testament almost disappeared, not because of an intention to eliminate them, but as an unintentional consequence of the old pattern for use of readings from the Old Testament.